Lighting for interior design. - Innes, Malcolm, ....- (London : Laurence King Publishing, 2012)
Without light, interior architecture cannot be fully designed and experienced. It is one of the key tools for an interior designer, but can be a dauntingly technical subject for students. This book takes a detailed, practical look at lighting in interior design, giving students all the key information and skills they need to be able to tackle lighting successfully in their designs.
With index, further reading and index